Building corporate reputation through corporate social responsibility: the mediation role of employer branding - Binu Raj, Asha; N., Akbar Jan; A.K., Subramani (International journal of social economics, 2022)
PurposeThe paper analyses the link between corporate social responsibility (CSR), employer branding (EB), and corporate reputation (CR). Considering the signaling theory and social commitment of organisations, the paper investigates the role of EB as a mediator.Design/methodology/approachData were collected through structured questionnaires from 684 employees from the Indian information technology (IT) sector. The conceptual model and hypotheses were tested using the structural equation modelling (SEM) approach.FindingsAs a part of employer attractiveness, the social value/social commitment of companies perceived as a result of CSR strengthens the CR. The results also suggest that EB mediates the relation between CSR and CR.Research limitations/implicationsThe paper contributes by integrating the CSR of organisations with their EB process for creating CR. Based on signaling theory, it further demonstrates scholarly value addition by providing a deeper understanding of the mediation effect of EB from a social commitment perspective. Scholars may further consider other stakeholders’ perspectives to test the role of CSR based on ethical/legal/environmental dimensions in building CR.Practical implicationsThe paper would help managers/employers invest in CSR activities, creating strong employer brands to attract various stakeholders. It will also help companies to focus on an attractive value proposition to attract various stakeholders, mainly job seekers.Originality/valueThis study extends the literature on CSR and EB by suggesting a statistically tested model of mediation of EB for creating CR. Furthermore, considering the signaling theory, the paper views CSR, CR, and EB from the employee’s perspective and explores their linkages.Peer reviewThe peer review history for this article is available at: https://publons.com/publon/10.1108/IJSE-09-2021-0541.